Diffuse Metastases in Bilateral Penile Corpus Cavernosum From Renal Cancer Diagnosed by 18F-FDG PET/CT. (June 2020) - Zou, Qiong; Jiao, Ju; Zou, Min-hong; Yang, Ting; Zhang, Yong
Abstract : Abstract: We report a rare case of a 60-year-old man with diffuse metastases in bilateral penile corpus cavernosum after radical nephrectomy for left renal carcinoma. 18 F-FDG PET/CT demonstrated diffuse hypermetabolic lesions in bilateral penile corpus cavernosum, hypermetabolic tumor recurrences in left renal operation region, and left pulmonary metastasis. Biopsy confirmed penile metastasis from renal clear cell carcinoma. Diffuse penile metastatic carcinoma from renal cancer is extremely rare and associated with poor prognosis. 18 F-FDG PET/CT is helpful for diagnosis of penis metastasis and accurate staging of primary cancer.